Dynamics of Sagittarius A: Examining Accretion Flow Elongation around the Milky Way’s Central Black Hole - Goshu, Belay Sitotaw (Budapest International Research and Critics University, 2024)
The dynamics surrounding Sagittarius A* (Sgr A*), the supermassive black hole at the center of the Milky Way, are thoroughly examined in this paper. The study investigates key parameters, including the density of accretion flow particles at varying radial distances, which reveal detailed insights into the structure and stability of the inflowing material. The velocity field surrounding Sgr A* demonstrates the acceleration patterns within the accretion disk, significantly influenced by the gravitational potential of the black hole. The overall density profile of the Milky Way’s central region, derived from accretion rates, further emphasizes the unique low-accretion characteristics of Sgr A*. Gravitational modeling illustrates the potential distribution and its effects on accretion flow distribution, enhancing our understanding of how matter behaves under extreme gravitational forces. Through histogram analysis of image data, we map the density variations around Sgr A*, revealing high-density regions and potential hotspots. Additional image processing identifies and isolates Sgr A*, allowing for a focused examination of its immediate environment. Lastly, the color cluster analysis relative to chemical abundances provides insights into the elemental composition near Sgr A*, and 3D surface plots and heatmaps depict the spatial structure and intensity distribution of galaxy clusters. Collectively, these findings enhance our understanding of black hole accretion mechanics, the impact of gravitational and magnetic forces, and the broader galactic ecology surrounding Sgr A*.